Role of Certified Registered Anesthetists (CRAs) in the Prevention and Management of Supine Hypotension during Cesarian Delivery under Spinal Anesthesia at the Tamale Teaching Hospital (TTH), Ghana - Danaah Malick, Martin Mumuni; Nyarko, Evelyn; Bamaalabong, Peter Paul (International Journal of Innovative Research in Medical Science, 2021)
Background: Supine hypotensive syndrome is a pathophysiologic state in a parturient after 20 weeks’ gestation when put in the supine position during cesarian section under spinal anesthesia. Spinal anesthesia produces rapid, effective, reliable and safe anesthesia making it the preferred technique for cesarian section. Maternal hypotension is a known common side effect of spinal anesthesia and is generally managed pharmacologically and/or non Pharmacologically. The aim of this study was to assess the management of supine hypotension during cesarean section under spinal anesthesia among CRAs at Tamale Teaching Hospital (TTH). Methods: A cross-sectional study with both quantitative and descriptive approaches were employed. Thirty-eight (38) CRAs were conveniently sampled and a structured self-administered questionnaire was used for data collection after pretesting for validity and reliability. Data was analyzed with Stata I/C. Results: Non-Pharmacological interventions: 19(50%) of CRAs placed parturient in the supine position n after spinal anesthesia with head up, 15 (39.5%) in Supine position alone, 4 (10.5%), used lateral position alone. Pharmacological interventions (Use of Intravenous fluids): Lactated Ringers solution 6(15.8%), Normal saline solution 24(63.2%), Crystalloid and colloid combination 8(21%). Vasopressor of choice: Ephephrine alone 36(94.8%), Phenylephrine alone 1 (2.6%), Multiple agents 1 (2.6%). Preferred intervention: non-Pharmacological 21(55.3%), Pharmacological 17(44.7%). Determinants of choice of intervention: Severity of hypotension 29(76.3%), availability of intervention 7(18.5%), diagnosis of the patient 1(2.6%), frequency of hypotension 1(2.6%). Conclusions: Most CRAs placed parturient in the supine position with head up as a non-pharmacological approach to managing supine hypotension after spinal anesthesia. Normal saline solution and ephedrine were widely used as pharmacological agents. Majority of the CRAs preferred using the non-pharmacological techniques as compared with the pharmacological approaches and their choice of intervention was significantly influenced by the severity of the intervention.